ANALYSIS OF ABILITY IN UNDERSTANDING MATHEMATICS CONCEPTS ON THE CIRCULAR MATERIAL OF STUDENTS OF CLASS VIII OF SMP NEGERI 2 BAY IN THE 2020/2021 STUDY YEAR - Robertus Daya (Afore : Jurnal Pendidikan Matematika, 2022)
This research is motivated by the ability to understand students' mathematical concepts which are still in the low category. This study aims to 1) describe the ability to understand mathematical concepts in the circle material for class VIII students of SMP Negeri 2 Telukdalam, 2) describe the students' difficulties in solving questions about the ability to understand mathematical concepts in the circle material. This research uses a type of qualitative research with descriptive research methods. The informants in this study were all students of class VIII SMP Negeri 2 Telukdalam, namely 25 people. Data were analyzed by data reduction, data presentation and conclusion. Research data collection techniques through tests of ability to understand mathematical concepts and interviews. The research findings showed that students were unable to restate the circle concept, students were unable to classify objects according to the nature of the circle, students were unable to distinguish examples of circles and non-circles, students were unable to select and use procedures or operations (formulas) according to the circle concept, and students still unable to apply the circle concept in solving simple problems.